Use of zeolites for the removal of H2S: A mini-review - Özekmekçi, Mehtap; Salkıç, Gözde; Fellah, Mehmet Ferdi (Elsevier, 2015)
Being a successful adsorbent for removal of hydrogen sulfide, zeolites should have good sulfur loading capacity, good regenerability and stable structure. These are natural zeolites having high adsorption capacity compared to other zeolites and synthetic zeolites. Zeolites can be modified by metals or metal oxides in order to increase their adsorption capacity. Removal of H2S is an essential process because it leads to corrosion in transport lines and poisoning of many catalysts even in low levels. Different types of adsorption methods such as fixed bed adsorption, pressure swing adsorption and sequential bed methods were experimentally used to investigate the removal of hydrogen sulfide. Computational methods (DFT) were also utilized theoretically. ETS-2 zeolite can be good choice to remove H2S due to its adsorbent properties. However this material has not been studied so much. Therefore more studies should be done experimentally and theoretically to examine the removal of hydrogen sulfide on excellent metal exchange forms of ETS-2. Consequently zeolites that have sulfur capacity increasing with modifications of metals or metal oxides are promising materials due to their high surface volume ratio which is one of the most important factors in adsorption. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: H2S; Hydrogen sulfide; Removal; Zeolite